Changes in the carboxyl-terminal domain of cytochrome b as a taxonomic character in Lutzomyia (Diptera: Psychodidae) - VIVERO, RAFAEL JOSÉ; CONTRERAS-GUTIÉRREZ, MARÍA ANGÉLICA; BEJARANO, EDUAR ELÍAS (Revista Colombiana de Entomología, 2009)
Morphological characters have been traditionally used for identification of sand flies of the genus Lutzomyia; however, their utility is limited in some species. In this work, we characterized the mitochondrial DNA region coding for the carboxyl-terminal domain of cytochrome b protein in seven species of Lutzomyia: L. trinidadensis, L. panamensis, L. cayennensis cayennensis, L. dubitans, L. gomezi, L. rangeliana and L. evansi. A total of 134 polymorphic sites were detected in the gene (40.98%) and 29 sites in the protein (26.6%). The very high level of polymorphism observed in cytochrome b, included replacement of amino acids, use of alternative stop codons, and differences in the size of the protein. The utility of the studied region in the identification of Lutzomyia species is discussed.